Validitas Media Interaktif Berbasis Aplikasi Android Untuk Meningkatkan Kemampuan Literasi Kelas 1 SD - May Yati; Titik Harsiati; Muh Arafik (Postgraduate, University of Mataram, 2023)
Literacy is a major component of school success, so students with deficits in reading skills generally experience a disadvantage in educational attainment. Reading is an activity to find meaning and writing that involves physical and mental activities. This is also in line with the opinion of) that Reading is one's mental process towards a text. In its narrow sense, reading means analyzing a text composed of letters and trying to interpret it as a whole. Learning to read according to is one of the most important skills children will acquire in the early years of school and difficulties in acquiring this skill can have adverse educational outcomes. there are still grade 1 Students whose reading skills are low, so there needs to be an effort made by the teacher in improving reading skills, one of which is using learning media. This study aims to create an interactive media product that is valid for use in early reading learning activities for grade 1 elementary school students. It is hoped that this developed product can help students learn to read. interactive media development using the Lee & Owen development model. products developed in validity by media, material, and language experts. the results of the product development validation test fall into the valid criteria and can be used to learn to read beginning. from the results of the interactive media validation carried out, it obtained a validity value of 81.66% in the